2019
DOI: 10.5152/turkjorthod.2019.18083
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic Treatment with Clear Aligners and The Scientific Reality Behind Their Marketing: A Literature Review

Abstract: Turkish Journal of Orthodontics (Turk J Orthod) is an international, scientific, open access periodical published in accordance with independent, unbiased, and double-blinded peer-review principles. The journal is the official publication of Turkish Orthodontic Society and it is published quarterly on March, June, September and December. Turkish Journal of Orthodontics publishes clinical and experimental studies on on all aspects of orthodontics including craniofacial development and growth, reviews on current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 34 publications
1
42
1
1
Order By: Relevance
“…Current literature guidelines [29,30] in the comparison between invisible aligners and traditional orthodontic devices propose a less enthusiastic view of clear aligners because although their effectiveness even in moderate complex cases is recognized, they would not be superior in terms of long-term stability of the result and would be more inefficient in correcting antero-posterior and vertical malocclusions [31]. In our study, in accordance with what is stated in the literature [32], treatments with clear aligners progress faster.…”
Section: Discussionsupporting
confidence: 87%
“…Current literature guidelines [29,30] in the comparison between invisible aligners and traditional orthodontic devices propose a less enthusiastic view of clear aligners because although their effectiveness even in moderate complex cases is recognized, they would not be superior in terms of long-term stability of the result and would be more inefficient in correcting antero-posterior and vertical malocclusions [31]. In our study, in accordance with what is stated in the literature [32], treatments with clear aligners progress faster.…”
Section: Discussionsupporting
confidence: 87%
“…In this context, previous studies reported positive changes and high satisfaction with Invisalign treatment especially with eating, chewing and appearance 19,36,37 . Invisalign treatment was associated with better satisfaction, better oral health related quality of life, and less negative impacts on oral health than fixed orthodontics [12][13][14][15][16]19,20,37,38 . They were associated with less disruption to eating and chewing and were rated as more satisfactory than fixed appliances 16 .…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, Invisalign and clear aligners were associated with less pain than fixed orthodontics [13][14][15][16] . This might be explained by that fixed orthodontic appliances could cause more tension, pressure, pain and sensitivity of teeth due to continuous force exerted by the appliance components.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recent years, more attentions have been paid to the effects of clear aligner on periodontal diseases due to its aesthetics and comfort on wearers [ 7 ]. As a new type of orthodontic treatment, clear aligner can cover all the teeth and keratinized gingiva without obvious damage to the periodontal tissues [ 8 ].…”
Section: Introductionmentioning
confidence: 99%